Botanical illustration : the essential reference - Grafton, Carol Belanger (Mieola, New York : Dover Publications, Inc., 2016)
"Comprising more than 500 years of printed botanical illustrations, this stunning compendium of black-and-white and color images includes medieval illuminated manuscripts, early woodcuts, hand-colored lithographs, Art Nouveau florals, and much more. Detailed bibliographies and artist biographies."--
Includes bibliographical references (pages 135-136) and index of artists.
Keywords: Botanical illustration; Botanical illustration -- Catalogs